The spreading simulation of molten Al alloy on Q235 steel in the first cycle of cold metal transfer process. (May 2016) - Lin, Qiaoli; Zeng, Chengzong; Cao, Rui; Chen, Jianhong
Highlights: Spreading was mainly affected by the distribution of temperature field. The advancing triple line was hindered by the solidified AlSi5 alloy. The wettability of AlSi5–Q235 was improved with the increase of heat input. Abstract: The volume of fluid and the solidification-melting models were used for the study of the wetting of Q235 steel by molten Al alloy in the first cycle of cold metal transfer process. Together with the consideration of the welding temperature field and the solidification process, the effect of welding temperature field (corresponding to the different wire feed speeds) on solidification, final wettability, and wetting behavior were discussed, respectively. The results showed that the molten Al alloy primarily began to solidify at the triple line, which is consistent with the distribution of temperature field; partial solidified metal blocked the motion of triple line to a certain extent; good wettability of Q235 steel plate by molten Al alloy can be observed with the increase of wire feed speed, and the advance of triple line was controlled by capillary force.